Relationship of x-ray parameters of the lower segmental lordosis and stability of sacroiliac joint at it’s dysfunction at conservative treatment - Korzh, Mykola; Staude, Volodymyr; Radzishevska, Yevgenya (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Objective: to study the X-ray parameters of the lower segments LIV –LV, LV –SI, lumbar lordosis in patients with sacroiliac dysfunction after conservative treatment and the relationship with sacrum, pelvis parameters in frontal plane which influence on the ability to walk. Methods: we examined 26 healthy volunteers who have regular sport activity and 51 patients (age 18–71 y. o.) before and after conservative treatment. Inclusion criteria were: pain syndrome more than 3 months in the area of spinae iliаca posterior superior, which irradiated into the groin, femur or gluteus; no effective previous conservative treatment; positive 4 or more than 6 provocative tests. We measured the angles of the cranial plane of sacrum tilt, pelvis and sacrum rotation around axial plane; the width of sacroiliac joint space in ventral, medial and dorsal parts; angles of lumbar lordosis and Albrecht angle — in sagittal plane, segmental lordosis LIV–LV, LV–SI on anterior-posterior X-rays. Results: in patients of the 1st group w e h ave f ound t he d ecreasing o f s acro-iliac joint space asymmetry in the ventral part; in the 2nd group of patients — alignment of joint space, decreasing of asymmetry in ventral part and its increasing in the dorsal part; in the 3rd group of patients there was — decreasing of asymmetry in the medial part; in the 4th group — tendency to the largest decreasing of asymmetry in the dorsal part. In all patients we observed the decreasing of pelvic and sacrum tilt, sacrum rotation. Conclusions: alignment of joint space, decreasing of pelvic and sacrum tilt, sacrum rotation in frontal plane and decreasing of segmental lordosis LIV–LV, LV–SI is indicated in patients with sacro-iliac joint dysfunction after conservative treatment. It allowed stabilizing of sacroiliac joint.